(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: The purpose of this study is to present Péter Dulai’s book and to introduce the outstanding murders of the Kádár era to all readers. Methodology: The article was prepared based on the analysis of the monography, it’s a book review. Findings: The violent crimes, homicides always deserve special attention. It is another matter which profession how views these crimes. It is disturbing but contains case studies with a twist for the professional and for lay reader as well. Value: The presented book describes crimes against life, without value judgments, with thorough and detailed source analyzes. By reading the book, we can not avoid asking the question of what motivations and circumstances led to the various cruel murders.